Formation of land for commercial uses - Kustovska, O.; Mudra, S. (Land Management, Cadastre and Land Monitoring, 2018)
The article analyzes the formation of land plots as the objects of the commercial use. It is established that the greatest value in the profitability of objects of commercial purpose is their placement and how correctly will be organized the using of the land plot for commercial purpose, especially in large cities.Key words: commercial purpose, land, land management projects, regulation mechanism, allocation procedure.